Influence of Frequency-Dependent Soil Models with Variable Water Content on Transient Responses of Overhead Transmission Lines - Pascoalato, Taina Fernanda Garbelim [UNESP]; De Araujo, Anderson Ricardo Justo; Kurokawa, Sergio [UNESP]; Filho, Jose Pissolato (Institute of Electrical and Electronics Engineers (IEEE), 2022)
This paper provides a short review and a comparison of three soil models, Scott (S), Longmire-Smith (LS) and Messier (M), where the effect of variation of water content on its frequency-dependent electrical parameters are considered. The transient performance of voltages developed for a lightning strike on a three-phase overhead transmission line (TL) above this type of soil are computed. The current is injected at the phase 1 and the voltages at receiving ends of phase 1, 2 and 3 are analyzed. Results demonstrated that the LS model result into the lowest values of the resistivity and relative permittivity for the same range of frequency and water content. As a consequence, the voltages at the phase 1 have no impact for these soil models whereas the induced voltages are strongly affected where the LS model provided an expressive reduction at the peaks.
Keywords: Electromagnetic transients; frequency-dependent soil; lightning performance; water content